Perlindungan Hukum bagi Kreditur atas Musnahnya Objek Jaminan Fidusia dalam Perjanjian Kredit Bank - Salsabila, Winalda Aulia; Badriyah, Siti Malikhatun (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
Banking credit agreements are generally accompanied by fiduciary security as a means of legal protection for creditors, particularly with respect to movable objects that remain under the control of the debtor. However, in practice, the destruction of the object of fiduciary security during the term of the credit agreement is not uncommon, whether due to force majeure, negligence, or unlawful acts committed by the debtor. Such circumstances have the potential to create legal uncertainty regarding the status of the credit agreement as well as the fulfillment of the rights and obligations of the parties. This research aims to analyze the legal position of credit agreements in the event of the destruction of the object of fiduciary security, as well as the forms of legal protection available to creditors in bank credit agreements. The research method employed is normative juridical research using statutory and conceptual approaches, with secondary data analyzed qualitatively. The results of the study indicate that the destruction of the object of fiduciary security does not extinguish the credit agreement nor the debtor’s obligation to repay the debt. Legal protection for creditors is realized through the provisions of the credit agreement, the obligation to insure the secured object, the registration of fiduciary security, the creditor’s preferential rights, and execution mechanisms as regulated under Law Number 42 of 1999 concerning Fiduciary Security. The fiduciary security legal system has provided adequate legal protection for creditors, provided that its implementation is carried out in accordance with the applicable laws and regulations.